Statut szkoły – między legitymizacją praw uczniów a przemocą wobec nich - Lysy, Joanna (Kortowski Przegląd Prawniczy, 2021)
The main issue addressed in this paper is a statute of Polish schools as a document in which students’ rights and violence are described, also according to them. Nowadays, there are many research connected to the violence in schools, however, these research are mostly focused on the violence between pupils or students. What about violence which is present in formal documents describing school’s rules and law? As an example, I would like to present some points from the school’s statute connected with students' rights and responsibilities as well as system of penalties and prizes.